Lack of effects of a "sobering" product, "Eezup!", on the blood ethanol and congener alcohol concentration. (September 2017) - Wunder, Cora; Hain, Sarah; Koelzer, Sarah C.; Paulke, Alexander; Verhoff, Marcel A.; Toennes, Stefan W.
Highlights: Sobering product Eezup is advertised to accelerate the rate of alcohol elimination. A Two-day crossover controlled drinking study (placebo vs. Eezup) was performed. Ethanol and congener alcohols were determined in blood during 9 h. Kinetic parameters Cmax, tmax, AUC and β60 were compared for Eezup and placebo. Results did not show a significant effect of Eezup. Abstract: Introduction: The lifestyle product 'Eezup!' appeared on the German market and promised to normalize energy metabolism. Among vitamins (B1, B2, B6, C, E and zinc), rice protein and fructose the addition of alcohol dehydrogenase and catalase enzymes is a novel approach. The product was advertised as capable of boosting the rate of alcohol elimination. Methods: Seventeen subjects (11 men, 6 women, 19–58 years old), participated in a two-way crossover drinking study. Unfiltered wheat beer (4.4 g% alcohol content) was drank within one hour to reach blood alcohol concentrations of 1‰ (1 g/kg whole blood). On one day "Eezup!" was taken according to the manufacturer's instructions before and after drinking which was substituted for a placebo on the second test day. Blood samples were taken during 9 h and ethanol and congener alcohols were determined. A comparison of Cmax, tmax, area under the curve (AUC) for ethanol and congener alcohols, and the hourly elimination rate of ethanol (β60 ) was performed to investigate an effect of Eezup!. Results: Ethanol concentrations (Cmax) were in the range of 0, 63–1, 00‰ (median 0, 85‰) and 0.62–1.22‰ (median 0.84‰) in the placebo and "Eezup!" condition, respectively, and not statistically different. Also tmax (1–2.5 h) and AUCs did not differ. The ethanol elimination rates were 0.16‰/h (0.14–0.19‰/h) and 0.17‰/h (0.14–0.22 ‰/h) in the placebo and "Eezup!" condition without significant difference. The pharmacokinetic parameters of the congener alcohols (1-propanol, isobutanol, 3-methyl-1-butanol, 2-methyl-1-butanol) as well as of methanol did also not differ. Conclusions: The results of the present study failed to show any effect of the sobering product "Eezup!" on the amount of ethanol and congener alcohols absorbed (Cmax, tmax, AUC) and on the ethanol elimination rate (β60 ).